Optimalisasi Kesejahteraan Dan Mutasi Dalam Meningkatkan Kinerja Karyawan (Studi Empiris Pada: Karyawan Pt Haleyora Powerindo Area Sukabumi) - Rahmat Setyo Wicaksono; Nor Norisanti; Sopyan Saori (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Advances in technology and information that are increasing rapidly, have a major impact on the economy, both in the trade, manufacturing, and service industries. This situation causes the competition between companies is getting tougher and companies are required to be able to compete. This makes human resources one of the most important assets in the survival of the company. Companies must be able to maximize the potential of existing human resources to produce optimal performance so that company goals can be achieved. However, there are problems in the study, namely the decline in employee performance which is thought to be caused by welfare and mutations that have not gone well. Researchers used a sample of 75 employees of PT Haleyora Powerindo Sukabumi Area Technical Services Section. The initial data collection was done by using interviews and direct observation. The data analysis technique used is multiple linear regression analysis with the help of Statistical Product and Service Solution (SPSS) software. The results of this study indicate that welfare (X1) partially has a positive and significant effect on employee performance (Y), and mutation (X2) partially also has a positive and significant effect on employee performance (Y). Keywords: Welfare, Transfer, Employee Performance